2020
DOI: 10.1142/s021827182050056x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of orbital orientations and radii on TianQin constellation stability

Abstract: TianQin is a proposed space-based gravitational-wave observatory mission to be deployed in high circular Earth orbits. The equilateral-triangle constellation, with a nearly fixed orientation, can be distorted primarily under the lunisolar perturbations. To accommodate science payload requirements, one must optimize the orbits to stabilize the configuration in terms of arm-length, relative velocity, and breathing angle variations. In this paper, we present an efficient optimization method and investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…To avoid these problems or mitigate their impact, very careful orbit optimizations and controls have been studied in a series of papers [74][75][76][77] . It was confirmed that choosing high Earth orbits can free TianQin from the disturbing effect of the nearby gravitational field of the Earth-Moon system, because the Newtonian gravity-field environment at 10 5 km from the Earth is fairly quiet and the effect of the Earth-Moon system's gravity field dominates at frequencies below 10 −4 Hz and falls off rapidly towards high frequencies 76 .…”
Section: Tianqin Projectmentioning
confidence: 99%
“…To avoid these problems or mitigate their impact, very careful orbit optimizations and controls have been studied in a series of papers [74][75][76][77] . It was confirmed that choosing high Earth orbits can free TianQin from the disturbing effect of the nearby gravitational field of the Earth-Moon system, because the Newtonian gravity-field environment at 10 5 km from the Earth is fairly quiet and the effect of the Earth-Moon system's gravity field dominates at frequencies below 10 −4 Hz and falls off rapidly towards high frequencies 76 .…”
Section: Tianqin Projectmentioning
confidence: 99%
“…There exist a few programs for the space-borne GW detectors [6,[35][36][37][38]. In this work, we constrain our focus on TianQin [35,39,40] (and LISA [6] when a network is considered). TianQin is expected to explore GW astronomy as well as fundemantal physics during its operation [8-12, 41, 42].…”
Section: Introductionmentioning
confidence: 99%
“…Such detections are also expected to put stringent constraints on deviation of general relativity or testing specific gravity theory [66,67]. Studies has revealed the availability of stable orbits that fulfills the requirement for GW detections [68][69][70][71]. The technology demonstration satellite, TianQin-1, has met the designed requirement [72].…”
Section: Introductionmentioning
confidence: 99%